Asesmen Literasi Sains Interaktif Berbasis Kearifan Lokal pada Platform Digital: Perspektif Framework PISA/AKMI: Interactive Science Literacy Assessment Based on Local Wisdom on a Digital Platform: A PISA/AKMI Framework Perspective - Rina Endang Sulistiowati; Evy Nur Rochmah; Juli Firmansyah (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Indonesia's science literacy score in PISA 2022 reached only 383, far below the OECD average of 489. At the local level, the science literacy achievement of *Madrasah Ibtidaiyah* (MI) students in Balikpapan City fell into the "Proficient" category, with an average score of 54. Existing assessment instruments are generic and fail to utilize local wisdom as a stimulus for authentic, contextual assessment. This study employed the Research and Development (R&D) method using Thiagarajan's 4D model (Define, Design, Develop, Disseminate). The instrument was developed based on the Ministry of Religious Affairs' AKMI framework, integrating Phase C Science and Social Studies (*IPAS*) learning outcomes with Balikpapan City's local wisdom as question stimuli, and was packaged interactively via Google Sites. Quality testing involved validation by four expert validators, readability and practicality tests with five teachers and five students, and a limited empirical trial with 30 students from the Balikpapan City MI Teacher Working Group (KKG). Expert validation scores ranged from 87% to 100% (highly feasible). Practicality was rated at 91% by teachers and 77% by students. The final prototype yielded 40 valid and reliable test items (KR-20 = 0.923), comprising 8 multiple-choice questions (L1: 20%), 18 Complex Multiple Choice questions, and 14 True/False questions (L2: 52.5% and L3: 27.5%), with a difficulty distribution of 42% easy, 55% medium, and 3% difficult. The science literacy assessment instrument—based on Balikpapan City's local wisdom and hosted on the Google Sites digital platform—proved valid, reliable, and practical for comprehensively measuring MI students' science literacy competence in accordance with the AKMI framework.